Successful vaginal delivery after 7 weeks of expectant management following twin-to-twin transfusion syndrome quintero v with marginal placenta previa: a case report - Santoso, Dhanny Primantara Johari; Nugrahani, Annisa Dewi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
There have been no cases reported twin-to-twin transfusion syndrome (TTTS) complicated with placenta previa. TTTS with prolonged intrauterine fetal death/IUFD could lead to neurological damage sequelae for another fetus. The management of TTTS varies. However, intervention resources availability needs to be considered and management of complex TTTS requires specific strategies. We report a case of A 28-year-old G4P1A2 of 8 months gestation presented with painless antepartum hemorrhage without labor signs. Fetomaternal ultrasound revealed: gemelli with lambda sign (+). The first fetus is alive, head presentation, 30-31 gestational weeks, marginal placenta inserted on the edge internal uterine ostium, single deepest pocket 8.5 cm, Cor 4 chambers view equal, renal, vesica urinaria, umbilical artery, middle cerebral artery-peak systolic velocity (MCA-PSV) were normal. The second fetus is a stuck twin and had been IUFD for 2 weeks. She had undergone expectative management with tocolytics, corticosteroid and MgSO4, as well as close and regular clinical and laboratory such as hematologic profile observations. At 37-38 gestational weeks, she came to outpatient polyclinic for a control. Vaginal delivery was arranged. The first baby was born normal; monitored regularly for 6 months, neurological complications and other sequelae were not found; monitored regularly, while the second baby was macerated (stage III). Expectative management followed by vaginal delivery since 37 weeks of gestation can be performed as indicated in TTTS Quintero V. Informed consent regarding neurological sequel in another fetus is necessary along with close and regular monitoring of the mother, fetus, and newborn to produce a better outcome.